1994
DOI: 10.1016/0378-5955(94)90026-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stimulus level on nonspectral frequency discrimination by human subjects

Abstract: Frequency difference limens were determined as a function of reference-stimulus level for pulsatile electrical stimuli in 5 postlingually deaf human subjects with Nucleus-22 cochlear implants and for sinusoidally amplitude-modulated acoustic white noise stimuli in 4 normal-hearing humans. Subjects were tested at levels throughout the dynamic range and extending to the lowest detectable levels. Response stability was measured over the course of 10 sessions. For electrical stimulation in the deaf ears, differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Results from pulse rate discrimination ͑Eddington et al., 1978;Pfingst, 1988;Pfingst et al, 1994;Townshend et al, 1987͒ and pulse rate identification ͑Lim and Tong, 1989;Tong and Clark, 1985͒ studies have been consistent with these findings in that performance has been markedly poorer at higher rates ͑Ͼ300-500 pulses/s͒ than at lower rates. There has, however, been considerable variability in performance across patients.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…Results from pulse rate discrimination ͑Eddington et al., 1978;Pfingst, 1988;Pfingst et al, 1994;Townshend et al, 1987͒ and pulse rate identification ͑Lim and Tong, 1989;Tong and Clark, 1985͒ studies have been consistent with these findings in that performance has been markedly poorer at higher rates ͑Ͼ300-500 pulses/s͒ than at lower rates. There has, however, been considerable variability in performance across patients.…”
Section: Introductionsupporting
confidence: 80%
“…Postlinguistically deafened cochlear implant patients are generally able to perceive pitch related differences in electric pulse rates in the range from about 50 to 300-500 pulses/s ͑Eddington et al., 1978;Lim and Tong, 1989;Pfingst, 1988;Pfingst et al, 1994;Shannon, 1983Shannon, , 1993Tong et al, 1983;Townshend et al, 1987͒. In studies using numerical estimation, pitch increases with increases in pulse rate up to 300-500 pulses/s and does not markedly change at higher rates ͑Lim and Tong, 1989;Shannon, 1983Shannon, , 1993Tong et al, 1983͒. Results from pulse rate discrimination ͑Eddington et al., 1978;Pfingst, 1988;Pfingst et al, 1994;Townshend et al, 1987͒ and pulse rate identification ͑Lim and Tong, 1989;Tong and Clark, 1985͒ studies have been consistent with these findings in that performance has been markedly poorer at higher rates ͑Ͼ300-500 pulses/s͒ than at lower rates.…”
Section: Introductionmentioning
confidence: 87%
“…In a review of 5 more recent studies from which data were obtained with a total of 19 subjects (Pfingst et al, 1994;van Hoesel and Clark, 1997;McKay and McDermott, 1999;McKay et al, 2000;Zeng, 2002), Moore and Carlyon (2005) reported an average rate difference limen of 7.3% at a rate of 100 Hz. However, the results varied greatly among subjects, and were also dependent on the details of the procedure applied in the experiments.…”
Section: Temporal Pitch Mechanismsmentioning
confidence: 99%
“…Modulation detection and modulation-frequency discrimination improve as a function of level throughout the dynamic range of electrical hearing (Pfingst et al, 1994;Fu, 2002). Therefore, the level of the stimulus must be taken into account in comparing modulation detection across various stimulus conditions.…”
Section: Introductionmentioning
confidence: 99%